Postural Discomfort Experienced by Women in Agricultural Activities: A Case Study in Dharwad District, Karnataka, India - , Renuka Salunke; , Suprita Pawar; , Shobha Huilgol; , Swati Vannur (Archives of Current Research International, 2025)
This study explores the postural discomfort experienced by women engaged in various agricultural activities across three regions: Mandihal, Mangalagatti, and Timmapur of Dharwad Taluk, Karnataka state. A total of 300 women (100 from each region) were surveyed to assess the discomfort in specific body parts such as the shoulders, wrists, hands, lower back, buttocks, upper legs, knees, and lower legs during activities including land cleaning, top dressing of fertilizer, sowing/transplanting, weeding, and cob removal. The study revealed that the most commonly reported discomfort occurred in the lower back and wrists, particularly during land cleaning, fertilization, and weeding. Standing, bending, and squatting postures were the primary causes of discomfort. The findings highlight the need for ergonomic interventions to reduce musculoskeletal discomfort and improve the well-being of women in agriculture. These results provide valuable insights for designing interventions aimed at reducing physical strain and promoting better health outcomes for female agricultural workers.